2013
DOI: 10.1139/cjm-2012-0465
|View full text |Cite
|
Sign up to set email alerts
|

Aminoglycoside resistance mechanisms in Pseudomonas aeruginosa isolates from non-cystic fibrosis patients in Thailand

Abstract: This study aimed to examine aminoglycosides (AMGs) resistance mechanisms, including the AMG-modifying enzyme genes, mexXY, rplY, nuoG, and galU, in the Pseudomonas aeruginosa non-cystic fibrosis (CF) isolates in Thailand. One hundred P. aeruginosa isolates from non-CF patients were examined for susceptibility to AMGs and for the presence of 10 AMG-modifying enzyme genes. Thirty randomly selected isolates were tested for transcription of mexXY and nuoG and mutations in rplY and galU. All the P. aeruginosa isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 23 publications
4
20
1
Order By: Relevance
“…According to the studies conducted in Latin America and Europe, 25-30% of P. aeruginosa isolates were also resistant to Ciprofloxacin[ 31,32]. In addition, we encountered a broad resistance rate against beta-lactams and aminoglycosides in P. aeruginosa strainswhich is in line with the results of previous studies[ 26,33]. On the contrary, others have described low resistance rates of P. aeruginosa against aminoglycosides is noteworthy that hospital acquired infections caused by MDR bacterial isolates are relatively frequent in developing countries such as Iran in comparison with developed nations such as the USA and most European countries.…”
supporting
confidence: 86%
“…According to the studies conducted in Latin America and Europe, 25-30% of P. aeruginosa isolates were also resistant to Ciprofloxacin[ 31,32]. In addition, we encountered a broad resistance rate against beta-lactams and aminoglycosides in P. aeruginosa strainswhich is in line with the results of previous studies[ 26,33]. On the contrary, others have described low resistance rates of P. aeruginosa against aminoglycosides is noteworthy that hospital acquired infections caused by MDR bacterial isolates are relatively frequent in developing countries such as Iran in comparison with developed nations such as the USA and most European countries.…”
supporting
confidence: 86%
“…Brazilian studies have also shown high rates of class 1 integron carriage (41.5% and 63.5%) in P. aeruginosa clinical isolates (15,22). Similarly, studies in Malaysia, Thailand, and Nigeria have shown that 60%, 69.3%, and 57% of P. aeruginosa clinical isolates harbored class 1 integrons, respectively (23)(24)(25). Two reports from Iran have shown the presence of class 1 integrons in 56.3% and 82.6% of P. aeruginosa clinical isolates, respectively (18,26).…”
Section: Discussionmentioning
confidence: 92%
“…Many mobile genetic elements such as plasmids, transposons, integrons, and phages are responsible for the horizontal gene transfer of antibiotic resistance. Recent studies suggest that integrons play a significant role in disseminating antibiotic resistance genes in clinical environments (6,7). Moreover, their role as a mobile genetic element in horizontal transfer of antibiotic resistance is proved (8).…”
Section: Introductionmentioning
confidence: 99%